2007
DOI: 10.1111/j.1477-8947.2007.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Global localism: Recentering the research agenda for biodiversity conservation

Abstract: Global environmental crisis narratives about biodiversity loss promote conservation research on how human activities impact natural resources and link scientific findings to protectionist policies. This paper critiques how local knowledge, over space and through time, is constructed for these studies and integrated with ecological measures and qualitative interpretations of biodiversity conditions. As a case example, we describe how ethnoecological research at Mt. Kasigau, a biodiversity hot spot in Southeaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…It is intuitively plausible that human communities that inhabit ecosystems rich in species also use a high number of species, and several studies have demonstrated just such a relationship (e.g., Begossi 1996, Salick et al 1999, Begossi et al 2002, Ladio and Lozada 2003, Ladio and Lozada 2004, Medley and Kalibo 2007, Thomas et al 2008, de la Torre et al 2009). Other studies have emphasized social, cultural, socioeconomic, and geographical factors as the main controllers of the number of species used by human communities (Ladio and Lozada 2001, Vandebroek et al 2004, Byg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is intuitively plausible that human communities that inhabit ecosystems rich in species also use a high number of species, and several studies have demonstrated just such a relationship (e.g., Begossi 1996, Salick et al 1999, Begossi et al 2002, Ladio and Lozada 2003, Ladio and Lozada 2004, Medley and Kalibo 2007, Thomas et al 2008, de la Torre et al 2009). Other studies have emphasized social, cultural, socioeconomic, and geographical factors as the main controllers of the number of species used by human communities (Ladio and Lozada 2001, Vandebroek et al 2004, Byg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…First, there has been a recent call in primatology to not exclude nonhuman primates living in human-modified habitats from our analyses [Chapman & Peres, 2001;Fuentes, 2006a]. This mirrors a broader call in conservation biology for greater scholarly engagement in interdisciplinary studies of human-influenced ecosystems [Bawa et al, 2004], as well as for scholars to move beyond a false compartmentalization of pristine vs. human-modified habitats [Medley & Kalibo, 2007] toward deeper examinations of how human social, cultural, and economic systems intersect with the ecological system [Robinson, 2006]. Second, conservationists are increasingly recognizing a mismatch between scientific research on wildlife, such as primates, and the information conservation practitioners actually need to better achieve conservation [Meijaard & Sheil, 2007].…”
Section: Introductionmentioning
confidence: 93%
“…More recently, local communities have moved off of Mount Kisagau's slopes down to its base. Despite a century of uprootedness, residents' lexicons retain the words to name and to describe the productivity and utility of many mountain plants, including those in the highland forest (Medley and Kalibo 2006).…”
Section: Landscape Formation and Forest Fragmentationmentioning
confidence: 99%